New developments in computable general equilibrium analysis for trade policy - Gilbert, John (Emerald, 2010)
The aim of the proposed volume will be to present new developments in the methodology and practice of CGE techniques as they apply to recent issues in international trade policy. The volume will be of interest to academic researchers working in trade policy analysis and applied general equilibrium, advanced graduate students in international economics, applied researchers in multilateral organizations, and policymakers who need to work with and interpret the results of CGE analysis.
Keywords: Equilibrium (Economics) -- Econometric models.; Commercial policy -- Econometric models.; elektronické knihy; electronic books